Understanding the role of user interface design in fostering students’ learning process in a multimedia courseware learning environment: insights from a Malaysian case study - Bashir, Kishabale (IIUM Journal of Educational Studies, 2018)
With the increased availability and use of information and communication tools in education, multimedia courseware design has gained the attention of instructors and multimedia developers in a bid to foster student learning. However, there is still scanty literature with regard to how user interface design of multimedia course environments fosters student learning process. The purpose of this study was to explore the perceptions students at a Higher learning institution in Malaysia on how user interface design fosters their learning process in multimedia courseware. This study adopted a qualitative design with semi-structured interviews as the data collection tool. Two postgraduate students participated in the in-depth interviews after learning from a multimedia module on how to use Excel software. Thematic analysis was used to derive meaning from students’ experiences with the learning courseware. From the interviews, it was found that the nature and usability of the interface design of multimedia courseware influences learning motivation, interactivity and cognitive load. The participants however identified software and hardware issues as the key challenges in using the multimedia courseware. Suggestions on how to improve future multimedia courseware were also noted. This research contributes to the area of E-learning by highlighting the need to design multimedia courseware interfaces that enhance student learning motivation, manage cognitive load and foster interactivity. It is thus recommended that further studies be carried on larger samples, using other research approaches and designs to allow for generalisability of the research findings on user interface design and learning process in multimedia courseware environment.